In the aftermath of genocide - Mandel, Maud, 1967- (My University, 2003)
France is the only Western European nation home to substantial numbers of survivors of the World War I and World War II genocides. In the Aftermath of Genocide offers a unique comparison of the country’s Armenian and Jewish survivor communities. By demonstrating how - in spite of significant differences between these two populations - striking similarities emerge in the ways each responded to genocide, Maud S. Mandel illuminates the impact of the nation-state on ethnic and religious minorities in twentieth-century Europe and provides a valuable theoretical framework for considering issues of transnational identity. Investigating each community’s response to its violent past, Mandel reflects on how shifts in ethnic, religious, and national affiliations were influenced by that group’s recent history. The book examines these issues in the context of France’s long commitment to a politics of integration and homogenization - a politics geared toward the establishment of equal rights and legal status for all citizens, but not toward the accommodation of cultural diversity
Armenians and Jews in twentieth century France
By Maud S. Mandel. - Durham ; London : Duke University Press, 2003. - xi, 317 p. ; 24 cm. - Includes bibliographical references (p. [291]-309) and index
Տվյալները՝ ինտերնետային կայքից
https://dokumen.pub/in-the-aftermath-of-genocide-armenians-and-jews-in-twentieth-century-france-9780822385189.html
Contents: 1. Orphans of the Nation: Armenian Refugees in France-2. The Strange Silence: France, French Jews, and the Return to Republican Order-3. Integrating into the Polity: The Problem of Inclusion after Genocide-4. Diaspora, Nation, and Homeland among Survivors-5. Maintaining a Visible Presence-6. Genocide Revisited: Armenians and the French Polity after World War II
Keywords: Holocaust survivors-France-Social conditions-20th century; Armenian massacres survivors-France-Social conditions-20th century; Jews-Cultural assimilation-France; Armenians-Cultural assimilation-France; Social integration-France; Holocaust, Jewish 1939-1945-Influence; Armenian Genocide, 1915-1923-Influence; France-Ethnic relations